Aceh's Multicultural Society in The Dutch Colonial Era: A Historical Study Of Modernization, Diversity And Inter-Ethnic Relations - Een Syaputra; Ririn Selvianti (Yupa: Historical Studies Journal, 2025)
This article aims to explain the modernization that occurred in Aceh during the Dutch colonial era and the diversity that emerged as a result of modernization, as well as to explain the relations between ethnic groups in Aceh during the Dutch colonial era, especially between the Acehnese and Minangkabau ethnic groups. This research is a library research with a descriptive analysis type. Modernization in Aceh during the Dutch colonial era occurred in at least three aspects, namely infrastructure modernization, especially highways and railways, economic modernization marked by the opening of large-scale plantations and educational modernization. The modernization of infrastructure, economy and education carried out by the Dutch in Aceh has caused a wave of migration from outside Aceh, thus having an impact on increasing ethnic diversity in Aceh. Relations between ethnic groups, especially between Acehnese and Minangkabau, have not been good, where there is negative prejudice from Acehnese people towards Minangkabau people due to historical prejudice factors, discrimination and excessive feelings of superiority.